Stratification of Javanese Language in Rural Areas of East Java and Its Implications for Javanese Language Learning - Mira Dwi Yana; Arief Sudrajat (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2025)
The purpose of this study is to describe the stratification of Javanese language use in rural communities in East Java and analyze its implications for Javanese language learning. This research is motivated by changes in the use of Javanese by the younger generation, which can weaken the value of polite language in social interactions. This study uses a descriptive qualitative approach, and data collection was conducted through interviews and observations. Data were obtained from several sources from several villages in East Java. The Communication Accommodation Theory (Giles) was used to study the patterns of convergence, divergence, and over-accommodation in language use. Data analysis was carried out through presentation, drawing conclusions, and reduction. The results of the study indicate that social status, age, and situational context influence the choice of Javanese language speech level. Divergence appears as an expression of the identity of the modern generation, the process of linguistic convergence shows the efforts of young speakers to adapt to societal standards of politeness. This study found that the use of Javanese is a social mechanism for determining closeness, status, and cultural identity, not just a linguistic system. The results of this study demonstrate the importance of learning polite language based on social context in formal education. By using these findings, teachers can create learning models that emphasize the social function of Javanese so that students understand not only the structure of the language but also the values of politeness and respect contained within it.